PARASITOLOGICAL INDICATORS OF CONTAMINATION AT SAND OF BEACHES AND MONITORING BY TRADITIONAL METHODS AND IMMUNOENZYMATIC ASSAY - Amaral, L. S.; Duarte, A. N.; Silva, V. L.; Pinna, L. C. L.; Sotero-Martins, A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Intestinal helminths are among the pathogens most often found in humans and can result in serious pathological, such as visceral larva migrans syndrome. Domestic animals serve as the natural hosts, but under certain conditions humans can acquire infection, developing an atypical cycle. Thus, the contamination for animal droppings in public spaces, such as beaches, poses risk factor in the transmission, increasing the incidence of these zoonoses. In this context, informations about environmental health is necessary because the monitoring would be the first step for treating unhealthy environments. Therefore, the study monitored the sand of beaches of two islands within Guanabara Bay, Rio de Janeiro state, was carried out by traditional methods (Lutz and Baermann) and the ELISA immunological test, in order to determine the level and the influence of seasonality on this contamination. Among the genera detected, Ascaris sp. and Ancylostoma sp. occurred with greatest frequency, functioning as important biological markers of environmental contamination. The highest frequency of parasite structures occurred in the summer, meaning a greater risk of disease transmission. The results evidence the high level of environmental contamination and the seasonal variations of this contamination. Additionally, the data obtained from ELISA confirm the sensitivity of this technique to detect cysts and oocysts of protozoa in the sand samples analyzed.